Advancing towards a tissue-engineered tympanic membrane: Silk fibroin as a substratum for growing human eardrum keratinocytes - Ghassemifar, Reza; Redmond, S.; Zainuddin; Chirila, T. (Sage Publications, 2010)
Human tympanic membrane cells (hTMCs), harvested from tympanic membrane (TM) explants, were grown in culture and then seeded on membranes prepared from silkworm (Bombyx mori) silk fibroin (BMSF) and on tissue-culture plastic membranes (PET). Fibroin was isolated from silk cast into membranes with a thickness of 10-15 µm. The hTMCs were cultured on both materials for 15 days in a serum-containing culture medium. The cells grown on both substrata were subjected to nuclear staining (DAPI) and counted. Further, the cultures were immunostained for a number of protein markers related to the epithelial/keratinocyte phenotype and cell adhesion complexes. The BMSF membranes supported levels of hTMC growth higher than that observed on the PET membranes. The immunofluorochemical analysis indicated unequivocally that BMSF is a more suitable substratum than PET with respect to the growth patterns, proliferation, and cell-cell contact and adhesion. BMSF appear as a promising substratum in the tissue-engineered constructs for the replacement of TM in case of nonhealing perforations.